2019
DOI: 10.20355/jcie29358
|View full text |Cite
|
Sign up to set email alerts
|

Language and Identity Development Among Syrian Adult Refugees in Canada: A Bourdieusian Analysis

Abstract: Framed by Bourdieu's work, this article focuses on the intersections between language learning experiences, capital, and identities of Syrian refugees now living in Regina, Saskatchewan. In this qualitative study, data were collected during a series of focus groups with Syrian women and men. Based on the study findings, we contend that the participants' multiple identities as hardworking, employed, independent, Muslim mothers or fathers, and wives or husbands developed in Syria were gradually eroded or altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Those following the empowerment and accommodation trajectories participate in something that could be called a second-language normalisation spiral: The more proficient learners on these trajectories are, the more they move into German-speaking contexts, study in German or engage in everyday small talk in German. Language acquisition becomes a way to fend off identity threats and re-establish identities previously cultivated in their home countries (Ghadi et al, 2019). Importantly, language proficiency and use, identification and position-taking as students and colleagues work together to stabilise this passage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those following the empowerment and accommodation trajectories participate in something that could be called a second-language normalisation spiral: The more proficient learners on these trajectories are, the more they move into German-speaking contexts, study in German or engage in everyday small talk in German. Language acquisition becomes a way to fend off identity threats and re-establish identities previously cultivated in their home countries (Ghadi et al, 2019). Importantly, language proficiency and use, identification and position-taking as students and colleagues work together to stabilise this passage.…”
Section: Discussionmentioning
confidence: 99%
“…A second strand of research complements the first strand by addressing these questions with a qualitative methodology. Ghadi et al (2019) show how adult Syrian refugees in Canada suffer from the multidimensional devaluation of their resources, including their linguistic capital, that is the value of their Arabic native language. These refugees' new living situations challenge long-held identifications as parents and as hardworking, deserving members of society.…”
Section: Research On Second-language Proficiencymentioning
confidence: 99%
“…We encourage other programs to consider developing a CLB-based badge system to help increase motivation and self-regulation among immigrant learners. Even though adult learners face many obstacles in their pursuit of a new language, they need language training that builds their confidence in the new language and culture, which will also rebuild their identities as contributing members of local and national communities (Ghadi, et al, 2019). A CLB-based badge system can provide them with greater direction and empowerment through their language learning journey.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that learning a language and attaining needed proficiency are key challenges for newcomers in gaining access to employment, pursuing further education, and integrating into the host community (Ghadi et al., 2019). As Masri and Abu-Ayyash (2020) stated: “The most important step in language acquisition is to understand the factors that lead to SLA [second language acquisition] and that lead to successful integration within a new society” (374).…”
Section: Making the Case: Contextual And Linguistic Factorsmentioning
confidence: 99%